Assessment of the Saccular Function in Children with Spastic Cerebral Palsy - Akbarfahimi, N.; Hosseini, S.A.; Rassafiani, M.; Rezazadeh, N.; Ghomsheh F. Tabatabai; Shahshahani, S.; Karimlou, M. (Нейрофизиология, 2016)
Our investigation was designed to assess the saccular function of the vestibular system upon
postural control dysfunction amongst children with spastic cerebral palsy (CP) using recording
of cervical vestibular evoked myogenic potentials (cVEMPs), as well as to compare such
findings with those in healthy subjects. Sixty two children (aged 7-12 years) were enrolled
and assigned into two groups. There were 31 cases of spastic CP with the functional levels of
I or II according to the Gross Motor Function Classification System in the patient group and
31 aged-matched healthy children as controls. The examined parameters were the latencies
of the P₁₃ and N₂₃ waves, P₁₃–N₂₃ peak-to-peak amplitude, amplitude asymmetry ratio (AAR)
and the cVEMP threshold. The cVEMP responses were recorded in 93.5 % of cases in the
CP group and in all healthy subjects. Only 51.6% of the CP-group cases were within the
normal AAR spectrum range. There were significant differences between the two groups with
regard to the N₂₃ wave latency (P < 0.001), P₁₃–N₂₃ wave amplitude (P < 0.001) and cVEMP
threshold (P<0.05). The significant difference in the cVEMP measured values between the
CP cases and healthy controls may be attributed to a motor development delay and deficits
in the vestibulo-collic reflex pathway. Our findings suggest that cVEMP recording may be
considered an auxiliary tool for the assessment of the vestibular system in children with
spastic CP. Such a test is expected to help more adequate planning for interventions. Метою нашого дослідження були оцінка сакулярної функції
вестибулярної системи при постуральній дисфункції у дітей, що страждають на дитячий церебральний параліч (ЦП),
з використанням відведення шийних вестибулярних викликаних міогенних потенціалів (cVEMP) та порівняння відповідних результатів із такими у здорових обстежених дітей.
62 дитини (вік сім–12 років) були розділені на дві групи
(31 дитина зі спастичною формою ЦП при функціональних
рівнях I та II відповідно до системи класифікації загальних
моторних функцій та 31 здорова дитина відповідного віку,
що складали групу контролю). Визначали наступні параметри: латентні періоди хвиль P₁₃ та N₂₃, амплітуди цих хвиль,
амплітуду від піку до піку коливань P₁₃–N₂₃, коефіцієнт асиметрії хвиль (AAR) та поріг cVEMP. Істотні cVEMP були
зареєстровані в 93.5 % випадків групи ЦП та в усіх здорових дітей. Тільки у 51.6 % дітей групи ЦП значення AAR
відповідали нормальному діапазону цього індексу. Середні величини латентного періоду N₂₃-хвилі, міжпікової амплітуди P₁₃–N₂₃ і порогу виникнення cVEMP у групах ЦП і
контролю вірогідно розрізнялися (P < 0.001, Р < 0.001 та
P < 0.05 відповідно). Істотна відмінність виміряних параметрів cVEMP у групах ЦП та здорових дітей може бути
пов’язана із затримкою моторного розвитку та дефектністю
вестибуло-двогорбикового рефлексу. Наші дані свідчать про
те, що відведення cVEMP може бути цінним допоміжним
прийомом при функціональній оцінці вестибулярної системи у дітей зі спастичним ЦП. Вірогідно, даний тест може
допомогти адекватніше планувати відповідні реабілітаційні заходи.